Thermal and spectral characteristics of quasioptical filtering devices for cryoelectronic receiving systems - Rudenko E. М.; Korotash, I.V.; Shapovalov А. P.; Tsybrii, Z.F.; Belogolovskii М.А.; Polotskiy, D.Yu.; Shlapak, Yu.V.; Chmil’ V. М.; Glushechenko, E.M.; Chmil’, V. V.; Pylypenko, A.M.; Sizov, F.F. (Reports of the National Academy of Sciences of Ukraine, 2015)
We discuss the use of polymer films as infrared-radiation filters. Numerical calculations of thermal characteristics of polymer films placed on a section of a circular waveguide are performed. It is shown that an additional coverage of such films with a layer with a high thermal-conductivity coefficient is needed for the realization of effective infra-red quasioptical filtering devices. Implementation of such composed structures allowed us to maximize a barrage from parasitic thermal re-radiation in the infrared region of the spectrum and the transmission with the least losses of an information signal in the operating microwave range 2–36 GHz.